2004
DOI: 10.1002/cbic.200400138
|View full text |Cite
|
Sign up to set email alerts
|

Fusarin C Biosynthesis in Fusarium moniliforme and Fusarium venenatum

Abstract: Fragments of polyketide synthase (PKS) genes were amplified from complementary DNA (cDNA) of the fusarin C producing filamentous fungi Fusarium moniliforme and Fusarium venenatum by using degenerate oligonucleotides designed to select for fungal PKS C-methyltransferase (CMeT) domains. The PCR products, which were highly homologous to fragments of known fungal PKS CMeT domains, were used to probe cDNA and genomic DNA (gDNA) libraries of F. moniliforme and F. venenatum. A 4.0 kb cDNA clone from F. venenatum was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
202
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(211 citation statements)
references
References 31 publications
8
202
0
1
Order By: Relevance
“…Microbiology 158 proteins can be grouped into three statistically supported clades, typified by the equisetin synthase of Fusarium heterosporum (EqiS; Sims et al, 2005), Gibberella moniliformis fusarinC (FusS; Song et al, 2004) and Cordyceps bassiana tenellin toxin (TenS; Eley et al, 2007)/Penicillium expansum cytochalasan synthase CheA/CytS (Schümann & Hertweck, 2007) (Fig. 4).…”
Section: P K Mukherjee and Others 160mentioning
confidence: 99%
“…Microbiology 158 proteins can be grouped into three statistically supported clades, typified by the equisetin synthase of Fusarium heterosporum (EqiS; Sims et al, 2005), Gibberella moniliformis fusarinC (FusS; Song et al, 2004) and Cordyceps bassiana tenellin toxin (TenS; Eley et al, 2007)/Penicillium expansum cytochalasan synthase CheA/CytS (Schümann & Hertweck, 2007) (Fig. 4).…”
Section: P K Mukherjee and Others 160mentioning
confidence: 99%
“…The F. graminearum genome encodes 15 polyketide synthases (PKS) 2 (2,3), of which FgPKS12 is the progenitor of nor-rubrofusarin/rubrofusarin/aurofusarin (4,5), FgPKS4 and FgPKS13 are the progenitors of zearalenone (1,6), FgPKS10 is the progenitor of fusarin C (7,8), and FgPKS3 is the progenitor of an uncharacterized black/purple perithecial pigment (8). PKS genes are typically found in gene clusters that comprise genes encoding transcription factor, transporters, and tailoring enzymes required for biosynthesis of the final product (1, 4 -6).…”
mentioning
confidence: 99%
“…A homologous gene of fusA in F. moniliforme is responsible for the early stages of fusarin biosynthesis in F. venenatum (Song et al, 2004 The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%